LINKING LEADER MEMBER EXCHANGE AND PERSON SUPERVISOR FIT WITH EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF EMPLOYEE WORK ENGAGEMENT - Venita Putri Utami; Muhammad Zakiy (Journal of Leadership in Organizations, 2020)
Closeness and compatibility between leaders and subordinates significantly affect the comfort of work, which results in employee performance. Through satisfaction in working, it can create employee engagement, which can contribute to improving employee performance. This study aims to determine the effect of leader-member exchange and personal supervisor fit on employee performance mediated by work engagement on Syariah Bank employees in the Special Region of Yogyakarta. The sample in this study amounted to 132 employees using purposive sampling techniques whose data collection uses cross-sectional analysis with the level of analysis of individual samples. This research uses Structural Equation Modeling (SEM) to analyze the data. The results showed that the leader-member exchange and person supervisor fit had a positive effect on work engagement, and work engagement had a positive impact on employee performance. Also, this study demonstrates that work engagement is able to mediate the positive influence of leader-member exchange and person supervisor fit on employee performance. For this reason, it can be said that work engagement is an antecedent that shapes employee performance, which is preceded by leader-member exchange and person supervisor fit.